“You are never a body alone” (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The interview with Sofia Neuparth brings the researcher's perspective on teaching-learning in dance based on the idea of an elastic training space. The creator has an important and unique career within contemporary art in Portugal.  In the late 1980s, she created a space for investigation, experimentation and creation based on studies of the body, movement and the commonplace: the c.e.m-centro em movimento ("center in movement").  In this testimony, Neuparth talks, above all, about her artistic trajectory, her study system in the “birth of gesture” and also about the c.e.m as a living and moving organism.
Keywords: Sofia Neuparth; contemporary dance; Lisbon; c.e.m-centro emm movimento